2007
DOI: 10.1158/0008-5472.can-06-1860
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Expression of a Dominant Negative Ku70 Fragment Radiosensitizes Human Tumor Cells under Aerobic and Hypoxic Conditions

Abstract: Ku70 is one component of a protein complex, the Ku70/Ku80 heterodimer, which binds to DNA double-strand breaks and activates DNA-dependent protein kinase (DNA-PK), leading to DNA damage repair. Our previous work has confirmed that Ku70 is important for DNA damage repair in that Ku70 deficiency compromises the ability of cells to repair DNA double-strand breaks, increases the radiosensitivity of cells, and enhances radiation-induced apoptosis. Because of the radioresistance of some human cancers, particularly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 47 publications
(62 reference statements)
1
49
0
Order By: Relevance
“…To measure the protein expression of CD, UPRT and mDsRed, protein samples (20 mg) from transiently transfected Cos7 cells, stably transfected R3327-CD/mDsRed and R3327-CD/UPRT/mDs Red cells were analyzed by Western blotting [20].…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the protein expression of CD, UPRT and mDsRed, protein samples (20 mg) from transiently transfected Cos7 cells, stably transfected R3327-CD/mDsRed and R3327-CD/UPRT/mDs Red cells were analyzed by Western blotting [20].…”
Section: Western Blotmentioning
confidence: 99%
“…Cells were treated with 5-FC or 5-FU (InvivoGen, San Diego, CA) at various concentrations for 24 h. After the drug treatment, cells were trypsinized, counted, serially diluted, and plated into 60 mm Petri dishes. After incubation for 10Á14 days, colonies were fixed, stained with crystal violet, and counted [20]. Surviving fractions were normalized to the plating efficiency of untreated controls.…”
Section: -Fc and 5-fu In Vitro Cytotoxicitymentioning
confidence: 99%
“…Similarly, mice with mutated Ku70 also display defect DNA repair and hypersensitivity to ionising radiation (15). Furthermore, experimental studies have shown that inhibition of DNA-PK cause radiosensitisation in vitro and in vivo (16)(17)(18)(19). This is in line with the central role of the DNA-PK complex in DNA repair, and forms the basis of pharmacological inhibitors that might become useful in cancer therapy in the future.…”
Section: Introductionmentioning
confidence: 75%
“…It is well established that genetic deficiency or inhibition of DNA-PK results in radiosensitivity of oxygenated cells [18,19,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%